Review. The use of cryopreservation for germplam conservation of vegetatively propagated crops - Gonzalez-Benito, M.E.=700 1 Clavero-Ramirez, I.; Lopez-Aranda, J.M.
(Es, En)
ilus., 100 ref.
Keywords: BANCO DE GENES; CONSERVACION DEL GERMOPLASMA; CONSERVACION BIOLOGICA; CULTIVO IN VITRO; NITROGENO; RECURSOS GENETICOS; ESPAÑA; CRIOCONSERVACION; RECURSOS FITOGENETICOS